Tumorigenic effects of human mesenchymal stromal cells and fibroblasts on bladder cancer cells - Frerichs, Lucie M.; Frerichs, Bastian; Petzsch, Patrick; Köhrer, Karl; Windolf, Joachim; Bittersohl, Bernd; Hoffmann, Michèle J.; Grotheer, Vera (Frontiers in Oncology, 2023)
Background Patients with muscle-invasive bladder cancer face a poor prognosis due to rapid disease progression and chemoresistance. Thus, there is an urgent need for a new therapeutic treatment. The tumor microenvironment (TME) has crucial roles in tumor development, growth, progression, and therapy resistance. TME cells may also survive standard treatment of care and fire up disease recurrence. However, whether specific TME components have tumor-promoting or tumor-inhibitory properties depends on cell type and cancer entity. Thus, a deeper understanding of the interaction mechanisms between the TME and cancer cells is needed to develop new cancer treatment approaches that overcome therapy resistance. Little is known about the function and interaction between mesenchymal stromal cells (MSC) or fibroblasts (FB) as TME components and bladder cancer cells. Methods We investigated the functional impact of conditioned media (CM) from primary cultures of different donors of MSC or FB on urothelial carcinoma cell lines (UCC) representing advanced disease stages, namely, BFTC-905, VMCUB-1, and UMUC-3. Underlying mechanisms were identified by RNA sequencing and protein analyses of cancer cells and of conditioned media by oncoarrays. Results Both FB- and MSC-CM had tumor-promoting effects on UCC. In some experiments, the impact of MSC-CM was more pronounced. CM augmented the aggressive phenotype of UCC, particularly of those with epithelial phenotype. Proliferation and migratory and invasive capacity were significantly increased; cisplatin sensitivity was reduced. RNA sequencing identified underlying mechanisms and molecules contributing to the observed phenotype changes. NRF2 and NF-κB signaling was affected, contributing to improved cisplatin detoxification. Likewise, interferon type I signaling was downregulated and regulators of epithelial mesenchymal transition (EMT) were increased. Altered protein abundance of CXCR4, hyaluronan receptor CD44, or TGFβ-signaling was induced by CM in cancer cells and may contribute to phenotypical changes. CM contained high levels of CCL2/MCP-1, MMPs, and interleukins which are well known for their impact on other cancer entities. Conclusions The CM of two different TME components had overlapping tumor-promoting effects and increased chemoresistance. We identified underlying mechanisms and molecules contributing to the aggressiveness of bladder cancer cells. These need to be further investigated for targeting the TME to improve cancer therapy.